A direct approach to nonuniqueness and failure of compactness for the SQG equation. (13th May 2021) - Isett, Philip; Ma, Andrew
Abstract: We give an alternative proof of the nonuniqueness of weak solutions to the surface quasigeostrophic equation (SQG) first shown in [3 ]. Our approach proceeds directly at the level of the scalar field. Furthermore, we prove that every smooth scalar field with compact support that conserves the integral can be realized as a weak limit of solutions to SQG.